Rising Concentration and Wage Inequality - Matias Cortes; Jeanne Tschopp (Institute of Labor Economics (IZA), 2020)
Wage inequality has risen in many countries over recent decades. At the same time, production has become increasingly concentrated in a small number of firms. In this paper, we show that these two phenomena are linked. Theoretically, we show that shocks that increase concentration will also lead to an increase in wage dispersion between firms. Empirically, we use industry-level data from 14 European countries over the period 1999-2016 and show robust evidence of a positive and statis-tically significant correlation between concentration and between-firm wage inequality, driven by increases in market shares and wages in high productivity firms.
Keywords: J31; L11; E24; 330; wage inequality; market power; heterogeneous firms; Europe